2014
DOI: 10.6028/jres.119.022
|View full text |Cite
|
Sign up to set email alerts
|

New National Air-Kerma Standard for Low-Energy Electronic Brachytherapy Sources

Abstract: The new primary standard for low-energy electronic brachytherapy sources for the United States is described. These miniature x-ray tubes are inserted in catheters for interstitial radiation therapy and operate at tube potentials of up to about 50 kV. The standard is based on the realization of the air kerma produced by the x-ray beam at a reference distance in air of 50 cm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 37 publications
1
29
0
Order By: Relevance
“…Through establishing an air-kerma rate calibration standard for eBT sources as opposed to the air-kerma strength calibration standard, 4 DeWerd et al identified necessary changes in the TG-43 dose calculation formalism for brachytherapy dosimetry. 7 In their modified protocol for eBT dosimetry, DeWerd et al suggested replacing the TG-43 dose-rate constant with a dose-rate conversion coefficient χ i , where i represents the applicator material with i = 0 referring to the bare source and χ 0 defined as the ratio of the dose-rate at 1 cm in water along the source transverse plane (i.e., the reference position) to the air-kerma rate at 50 cm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through establishing an air-kerma rate calibration standard for eBT sources as opposed to the air-kerma strength calibration standard, 4 DeWerd et al identified necessary changes in the TG-43 dose calculation formalism for brachytherapy dosimetry. 7 In their modified protocol for eBT dosimetry, DeWerd et al suggested replacing the TG-43 dose-rate constant with a dose-rate conversion coefficient χ i , where i represents the applicator material with i = 0 referring to the bare source and χ 0 defined as the ratio of the dose-rate at 1 cm in water along the source transverse plane (i.e., the reference position) to the air-kerma rate at 50 cm.…”
Section: Discussionmentioning
confidence: 99%
“…The Lamperti chamber geometry was simulated according to design specifications from Boutillon et al 5 as described by Seltzer et al, 4 A schematic representation of the Lamperti chamber is shown in Fig. 2(b).…”
Section: C1 Lamperti Chambermentioning
confidence: 99%
“…The air-kerma rate standard was accomplished through the introduction of the Lamperti Free Air Chamber (7). The NIST determination of the air-kerma rate standard for the Xoft model S700 source is the subject of a recently published NIST journal article (8). In 2014, the air-kerma rate at 50 cm _ K 50cm was transferred from NIST to the UWADCL to establish a well chamber calibration service.…”
Section: Introductionmentioning
confidence: 99%
“…The following materials have been recommended in two review articles for energies down to 50 kV:A150, Gammex Solid Water™/ RMI-457/WT1, MS11, PAGAT, Plastic Water® DT, Plastic Water LR, PTW RW1 and Virtual Water. Unsuitable materials include: Perspex/polymethyl methacrylate (PMMA), Plastic Water, Polystyrene, PRESAGE, RW3 11,39 (the reader is advised to refer to the original sources for details of composition and 40 and a German/Czech collaboration in Europe. There is also a desire to derive new codes of practice based on direct dose-to-water calibration, with consistent quantities and a clear transition from current methods.…”
Section: Output Calibrationmentioning
confidence: 99%